The Three Postulate Idea: Between Limits and Metaphysical Beliefs in Immanuel Kant's System of Philosophy - Daunan, Duncan Matthew (Riviera Publishing, 2024)
In the history of Western philosophy, debates about truth and error have continued to develop, reflecting diverse views that have emerged over time. The question of human nature became the center of intellectual attention, expanding philosophical study from speculation to fundamental thinking. Amid this context, Immanuel Kant emerged as a key figure who brought a new approach to philosophical inquiry. Although he spent his life in Koningsberg, his ideas in epistemology, anthropology, ethics, and education gained global recognition and made him one of the most influential philosophers of the modern era. However, his views have also drawn criticism, especially for the inconsistencies that are perceived to support dogmatism, although he originally intended to criticize it. This research analyzes Kant's thought, especially about the limits of human knowledge, metaphysics, and criticism of dogmatism. The method used is qualitative text analysis, which examines Kant's main work,